Instytucjonalne poradnictwo zawodowe na przykładzie Gorzowa Wielkopolskiego = Institutional career guidance using the example of Gorzów Wielkopolski - Pilecka, Dorota (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The goal of this publication is to present institutional career guidance with a mediumsized town as the example. It has been written based on the research carried out in the framework of the Master`s thesis entitled ?Organization of vocational guidance in mediumsized towns; example of Gorzow Wlkp.?, under the guidance of Professor Zdzisław Wołk of the University of Zielona Gora (14 June 2007).
Keywords: poradnictwo zawodowe; Gorzów Wielkopolski